PEMBELAJARAN SQ3R BERBANTUAN BUKU CERITA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR DAN MEMBACA KRITIS PESERTA DIDIK KELAS V SEKOLAH DASAR DI KECAMATAN MADANG SUKU II OKU TIMUR - Sutriyanto; Erwin; Isti rokhiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the lack of teachers' understanding in implementing appropriate learning models to enhance thinking and critical reading skills in Indonesian language learning. The study aims to examine the effect of the SQ3R learning model on the thinking and critical reading skills of fifth-grade students in Madang Suku II District, OKU Timur. This research employs a quantitative method with a true experimental design (Pretest-Post-test Control Group Design). The population consists of fifth-grade students from 25 elementary schools in Madang Suku II District, with a sample of 39 students from SD Negeri 1 Riang Bandung selected using probability sampling. Data were collected through tests, observations, and documentation and analysed using a t-test with SPSS. The results indicate that the implementation of the SQ3R model has a significant effect on thinking skills (t-value = 4.195 > t-table = 2.021) and critical reading skills (t-value = 3.533 > t-table = 2.021). Additionally, the SQ3R model assisted by storybooks has a strong impact on thinking skills (Cohen’s d = 1.12) and critical reading skills (Cohen’s d = 0.99). Therefore, the SQ3R model is effective in enhancing the thinking and critical reading skills of fifth-grade students.